Syphilis of the lumbar spine: A case report and review of the literature. Issue 50 (December 2017) - Yin, Ruofeng; Wang, Liping; Zhang, Tinglong; Zhao, Baolin
Abstract: Rationale: Tertiary syphilis can manifest as gummatous disease, but gumma of the spine has been extremely rarely reported. Patient concerns: A 61-year-old male complained of worsening pain and numbness in both lower legs for four weeks. Diagnoses: Syphilis of the Lumbar Spine. Interventions: Pedicle screw fixation (L3-S1) and posterior decompression of the vertebral canal at L4-5 were performed. Outcomes: The postoperative VAS score of both lower extremities decline to 2 from 7 at admission. Dorsal thumb extensor motor power (left/right) at day 7 postoperatively was 3/3 ( versus admission: 1/1). Laboratory examinations showed normal white blood cell count ( versus admission: 13.8 × 10 9 /L; reference value: 4.00−10.00 × 10 9 /L) and decline in C-reactive protein (20.35 mg/L versus admission: 77.43 mg/L; reference value: 0.00−10.00 mg/mL) and ESR (58 mm versus admission: 73 mm; reference value: 0–15 mm). Lessons: Our case illustrates that although gummatous disease of the spine may be extremely rare, it should be considered in the differential diagnosis of tuberculosis or malignancy of the spine so as to avoid a wrong diagnosis and incorrect treatment.